Characterization, expression and function analysis of anthocyanidin reductase gene from Vitis vinifera L. cv. Cabernet Sauvignon under UV-C irradiation. Issue 1 (1st January 2021) - Niu, Tiequan; Li, Changhen; Yang, Bo; Zhang, Pengfei; Fan, Weixin; Wen, Pengfei
Abstract: Flavonoids are important polyphenols, and widely distributed in plants. Anthocyanidin reductase (ANR), a precursor enzyme in (-)- epicatechin synthesis, could play an important role in anthocyanins biosynthesis. In the present study, the ANR gene was cloned from Vitis vinifera L. cv. Cabernet Sauvignon. Compared with VvANR (GenBank Accession No. NM_001280956.1), they differed in only 4 bp and shared similarity of 99.6%. The ANR protein belongs to the cl33424 Superfamily. In addition, many light-responsive elements and abiotic stress-related elements (ABRE, MYB, WRKY, etc.) were found in the promoter region of the ANR gene. STRING analysis predicted that VvMYBPA1 and VvMYBPAR may be involved in regulating the expression of the ANR gene. Different UV-C irradiation times were used for Cabernet Sauvignon berries during grape berry development, and the comparison analysis showed that UV-C irradiation improved significantly the accumulation of catechin and epicatechin during 20–50 days after full bloom, especially, under UV-C irradiation for 5 min. Furthermore, UV-C irradiation for 5 min had a greater effect on the expression of the ANR gene, the accumulation of catechin and epicatechin, and the enzymatic activity of ANR than UV-C irradiation for 10 min. Through the virus-induced gene silencing system, the ANR-silenced grape leaves were chlorotic, in which the contents of catechin and epicatechin were both significantly lower than those in the control, showing a very significant difference, respectively. In summary, our results demonstrated that the ANR gene played a crucial role in the accumulation of epicatechin in grapes, and its expression was upregulated by UV-C irradiation.